KESESUAIAN LAHAN PERMUKIMAN TERHADAP RENCANA TATA RUANG WILAYAH BERBASIS SIG DI KABUPATEN KEPULAUAN SANGIHE - Sofiena Mei Nessa; Selvana Treni Rosita Tewal; Cahyadi Nugroho (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
The problem in this study is related to the number of developments, especially those aimed at their designation, which is not by the existing regional spatial plan. This is because many developments are located in disaster-prone areas, coastal border areas, and protected areas. This also triggers changes in land use that are quite large from time to time. This study aims to determine the use of utilization with a regional spatial plan. This study uses quantitative methods to determine developments based on data in the Sangihe Islands Regency, analyzing image data and knowing the level of suitability of land use with the RTRW. The method of analysis in this study uses a method of spatial analysis based on geographic information systems (GIS) using supervised classification, scoring, weighting, overlay. The variables in this study include land use, spatial planning, and adjustments. The results show that the land area in the Regional Spatial Plan is suitable for land use in particular for an area of ​​3,202.65 hectares and not suitable for an area of ​​17,946.03 hectares from the total area of ​​the existing land use.